Aripiprazole in the acute and maintenance phase of bipolar I disorder - Zupancic, Melanie (Dove Medical Press, 2012)
Bipolar affective disorder is a disabling illness with substantial morbidity and many management challenges. Traditional mood stabilizers such as lithium, valproate, and carbamazepine are often inadequate in controlling symptoms both during the acute and maintenance phase of treatment. Aripiprazole is a second-generation antipsychotic with a unique mechanism of action. Evidence suggests that it is effective in acute manic and mixed states. There are limited data to suggest its efficacy as a maintenance agent. Future studies will be needed to better define the role of aripiprazole relative to other traditional pharmacologic agents.